Media Framing of the Israel-Palestine Conflict: A Critical Discourse Analysis of Aljazeera and CNN Instagram Account - Luhulima, Celine Christina; Linuwih, Endar Rachmawaty (PROJECT (Professional Journal of English Education), 2025)
This research aims to see how a media displays an ideology by framing the discourse of an issue. The data in this study are words and sentences in captions that represent how the Palestinian-Israeli conflict is reported through the Instagram accounts of CNN (@cnn) and Aljazeera (@aljazeeraenglish) news channels. In this research, the author uses qualitative methods to collect and review the findings. The data is analyzed using Critical Discourse Analysis by Van Dijk which includes macro structure, superstructure, and micro structure. Based on the results of the data analysis, it can be concluded that there are differences in the way the Palestinian-Israeli conflict is represented. This shows that each media channel from both @aljazeeraenglish and @cnn on average reflects their respective ideologies by using their views on the conflict to frame an event. In general, it can be seen that the way the @aljazeeraenglish account frames an event is indirectly impartial and uses several words that express criticism regarding the conditions that occur in Palestine. While on the @cnn account, they frame the news directly factually, and optimistically without taking sides.  The use of words in news strongly influences how a media account carries the ideology it wants to convey.